2010
DOI: 10.1243/17543371jset66
|View full text |Cite
|
Sign up to set email alerts
|

Effect of friction on tennis ball impacts

Abstract: There are currently no restrictions on the coefficient of friction of tennis courts or strings. The aim of this paper was to determine the effect of friction on tennis ball impacts. Finite element models were used to determine the effect of friction for oblique spinning impacts both between a tennis ball and a rigid surface and between a tennis ball and the string bed of a freely suspended racket. The results showed that during an oblique impact a tennis ball can behave in any of the following ways: first, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 20 publications
1
23
0
1
Order By: Relevance
“…For a COF below 0.60, the horizontal force is proportional to the normal force, suggesting that the ball is sliding throughout the bounce without changing the friction force direction. For a COF above 0.60, the frictional force drops to 0 after 4 to 5 ms (indicating that the ball is rolling at that point) and then even reverses sign (similar results are reported by Allen, Haake, & Goodwill (2010) for tennis ball bounce). This indicates that the ball is slipping or over-spinning, means that the horizontal velocity of the ball is smaller than the product of its radius and its angular velocity.…”
Section: Effect Of the Cofsupporting
confidence: 81%
“…For a COF below 0.60, the horizontal force is proportional to the normal force, suggesting that the ball is sliding throughout the bounce without changing the friction force direction. For a COF above 0.60, the frictional force drops to 0 after 4 to 5 ms (indicating that the ball is rolling at that point) and then even reverses sign (similar results are reported by Allen, Haake, & Goodwill (2010) for tennis ball bounce). This indicates that the ball is slipping or over-spinning, means that the horizontal velocity of the ball is smaller than the product of its radius and its angular velocity.…”
Section: Effect Of the Cofsupporting
confidence: 81%
“…Very recent research has identified a critical hole area ratio, which is the ratio of dimpled hole area to the total shoe contact area, for tennis shoes sliding on a hard court [81]. Allen et al [82] showcase the effect of friction on tennis ball impacts.…”
Section: Friction In Sportmentioning
confidence: 99%
“…In comparison, t decreases as s decreases for shallower impacts because of the increased movement of the strings over each other rather than the decrease in friction between the ball and strings. Equation (3) should be used carefully to determine the coefficient of friction since it represents traction rather than the more traditional sense of Coulomb friction, as stated by Allen et al 10 The effect of changing the coefficient of friction of the tennis strings is more complex than initially envisaged. The instinct is that a reduction in s might reduce the friction of the ball travelling over the surface.…”
Section: Effect Of Inter-string Frictionmentioning
confidence: 99%